'Gott Strafe England': Ivor Gurney's Strafes and Ways. (31st October 2021) - Brooks, Martin
Abstract: This essay describes Ivor Gurney's use of the word 'strafe' in his poems of the First World War. At the outbreak of the War, the word was a new arrival in the English national consciousness. It had come to prominence in the German Army's slogan, ' Gott strafe England ' ('God punish England'). Allied counterpropagandists soon redeployed this slogan as evidence that the German people were hateful and frenzied, and it gained currency as an informal English noun for a German artillery bombardment. In poems dating from during and after the War, Gurney draws on 'strafe's' interlinguistic existence to express his contempt for the two powers' propaganda. In treating the word as fluctuating between two languages, Gurney stages his separation from both English and German narratives of nationhood. Tracking his use of the word 'strafe' shows how he described the importance of individual experiences for understanding the War, portrayed a sense of 'Wonder' that he suggested could define soldier poets, and expressed his post-war belief that England had betrayed him. By outlining how Gurney attached these possibilities to 'strafe', this essay contributes to the wider critical understanding of how and why he wrote about his War experiences.